Women’s and Men’s Status: Revisiting the Relationship Between Gender Equality and Intimate Partner Violence Against Women in Europe - Gómez-Casillas, Amalia (Journal of interpersonal violence, 2023)
The first European Union Survey on Violence against Women (EU-VAW) released in 2014 revealed the unexpected result indicating that the world’s most egalitarian countries have relatively high rates of Intimate Partner Violence Against Women (IPVAW). This phenomenon, referred to as the “Nordic Paradox,” revived a heated, intermittently ongoing discussion dating back four decades where several competing hypotheses about the relationship between gender inequality and IPVAW have been proposed, but no consensus has been reached. The main aim of this paper is to revisit the most important of such hypotheses proposed in the last four decades, while proposing a new one that could potentially throw some light on understanding the “Nordic Paradox.” Multilevel linear regression models are estimated using data from the EU-VAW survey conducted in 2012, and an alternative operationalization of the Gender Equality Index (GEI) (our measure of gender equality). We did not find any significant effect of gender equality on IPVAW repetition. However, we found that higher country-level status of women and men go together with less IPVAW, with a larger effect of women’s status in economic domains compared to the impact of men’s economic status, and a larger effect of men’s overall status. These findings support the Marxist feminist hypothesis, stating that women’s absolute status in the economic and labor domain is critical in lessening IPVAW, as women’s real and potential access to resources is key for leaving a violent relationship. At the same time, our results support the “male privilege protection” hypothesis, which states that gains in women’s status in certain domains—such as in the economic sphere considering our results for the European Union—would not suppose a threat to men, allowing ameliorative effects. In contrast, if the overall status of men is threatened, backlash effects would be triggered.